Farmer’s Varieties in India- Factors affecting their preferential prevalence and the current status of their legal protection - SINGH, R P; AGRAWAL, R C (The Indian Journal of Agricultural Sciences, 2019)
In India, both High Yielding Varieties (HYVs) and Farmers’ Varieties (FVs) are being cultivated in different seasons in various agro-ecosystems in all regions of the country. A review of the contemporary literature reveals that a large number of factors namely, institutional, environmental, socio-economical and technical, determine the choice of a particular kind of variety (HYVs vs FVs). Literature also supports the fact that FVs are adapted better under marginal and low-input environment, due to their inbuilt resilient mechanisms. A large number of FVs of various crops continue to be grown in different states, occupying significant area in different regions and seasons. Also, the contribution of FVs is significant for food and nutritional security, particularly for small and marginal farmers in low-input marginal conditions. With regard to the legal protection of FVs, in case of food grain crops (cereals and pulses), almost all registration of FVs for Plant Variety Protection (PVP) have been for self-pollinated crops by virtue of being homogenous and qualifying the distinctiveness, uniformity and stability (DUS) test for their protection and conservation through legislative mechanism in India. The present study reveals that in case of coarse cereals, vegetables and cash crops, the registration of FVs for PVP are very low/negligible, due to relatively more variability/heterogeneity by virtue of their genetic makeup and pollination behaviour, thus failing to qualify DUS test. The present analysis indicates that provisions under Protection of Plant Varieties and Farmers Rights Act (2001) need further amendment so that important FVs are not excluded from getting intellectual property right protection.